Penerapan Algoritma Welch-Powell Pada Penyusunan Jadwal Perkuliahan di Program Studi Pendidikan Matematika - Ririn Mufidatur Rohmawati; M. Ivan Ariful Fathoni; Ismanto Ismanto (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
Graph theory can be applied in course scheduling. The problem discussed in this study is scheduling courses in the UNUGIRI Mathematics Education Study Program using graph coloring. The purpose of this study is to prevent the occurrence of overlap (cross-over) in the preparation of courses. Good scheduling is a schedule that can be carried out by all related parties in teaching and learning activities. The algorithm used in this study is the Welch-Powell algorithm. The research was conducted using an axiomatic deductive method by deriving existing axioms or theorems, then applied to vertex coloring on the graph representation of the lecture scheduling of the UNUGIRI mathematics education study program. The readiness matrix to teach odd-semester courses is obtained based on the Welch-Powell algorithm. 2022/2023 with six different colors. The six colors represent the scheduling of 26 UNUGIRI Mathematics Education Study Program courses into six days without any cross-over.